Multiculturalismo, discurso e identidade em cartas dos leitores de língua inglesa - Coimbra, Alda Maria (2008)
Departing from a socio-construcionist point of view of discourse and social identity and also using Multiculturalism and Multicultural Education principles, as well as Critical Pedagogy fundamentals and studies of Critical Discourse Analysis, the proposal of this thesis was to investigate analytical dimensions to conduct a critical analysis of the genre letter to the editor published in The New York Times on-line. The two main lines of reflections implemented were the Critical Multiculturalism (LAWTON, 1983, 1989; MCLAREN; GIROUX, 2000; SACRISTÁN, 1995) to select the themes of the letters and the Critical Discourse Analysis (CHOULIARAKI; FAIRCLOUGH, 1999; FAIRCLOUGH, 1989, 1992/2007, 1995, 2001, 2003) to define the analytical dimensions: discursive, social and textual. The discursive dimension was investigated through the analysis of the conditions of production, distribution and consumption of the letters and the development of intertextuality. The social dimension was explored through the investigation of how social relations, social identities and social systems of knowledge and belief are questioned, reproduced, reinforced or (de) constructed. The textual dimension was investigated through the exploration of the main elements of grammatical and lexical structures that contribute to the construction of meanings. The application of these dimensions revealed how language is used to reach discursive objectives of writers and favored the examination of social inscriptions of language and meanings that underlie discourse. The study of these dimensions can be considered a potential contribution to the teaching/learning committed to the formation of reflexive agents. Therefore, this research should be conceived as a possible collaboration, in a micro level, to a critical approach to the teaching/learning of foreign language whose objective is to participate in the development of a socially responsible educational practice.